The Sacred Complex of Kashi: A Microcosm of Indian Civilization - ., K.T.K (Journal of Dharma, 1980)
L .L. P. Vidyarthi, B. N. Sarswati and Makkan Jha, The Sacred Complex of Kashi : A Microcosm of Indian Civilization, Delhi: Concept Publishing Company, 1979, pp. 319, Rs. 80.